Pengembangan Instrumen Literasi Sains Kontekstual Bencana Alam (Gempa Bumi dan Gunung Api) : Development of Contextual Science Literacy Instruments for Natural Disasters (Earthquakes and Volcanoes) - Nuryanti, Alimah; Kaniawati, Ida; Suwarma, Irma Rahma (PendIPA Journal of Science Education, 2025)
This study aimed to develop a valid and reliable scientific literacy test instrument for seventh-grade junior high school students on earthquakes and volcanoes. The method used is Research and Development with a 4D model, which includes the stages of define, design, develop, and disseminate. The research subjects consisted of 30 junior high school students. The development data were analyzed to assess the validity, reliability, difficulty level, and discriminatory power of the instrument. The development procedure included planning, preparation of the initial draft, validation of content and construct by experts through the suitability of scientific literacy indicators with the test items, followed by field trials, revisions, and implementation of the instrument. Based on 15 test items prepared, 13 were declared valid, one was revised, and one was not used. The analysis results showed the reliability of the instrument with a KR-20 coefficient of 0.76 which is included in the high category. The level of difficulty of the questions consisted of 12 items in the medium category and 3 items in the easy category, while the discriminatory power of all questions was in the very good to good category.